2020
DOI: 10.1177/2515690x19900883
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Activity of Ethanolic Leaf Extract ofPaullinia pinnataLinn (Sapindaceae) inShigella flexneri–Induced Diarrhea in Wistar Rats

Abstract: Herbal products from Paullinia pinnata Linn are widely used in African folk medicine to treat several infectious diseases. Although the extracts from this plant has been shown to possess antimicrobial potential, their activity in infectious diarrhea is less reported. Diarrhea was induced by oral administration of 1.2 × 109 CFU/mL of Shigella flexneri to the rats. The infected rats were treated for 5 days with the doses of 111.42, 222.84, and 445.68 mg/kg of P pinnata. The level of biochemical parameters was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
1
1
Order By: Relevance
“…Since the methanol leaf extract of Paullinia pinnata did not show any sign of toxicity against A. salina at 10, 100, and 1000 µg/mL, it implies that the extract may have no anti-tumor, pesticidal, anti-Trypanosoma cruzi or antifungal properties. This observation is inconsistent with the findings of the study conducted by de Dieu Tamokou et al (15), which showed that P. pinnata leaves had anticancer properties. This may be because these investigators employed various specific cancer cell lines, suggesting that cancer cell lines are more sensitive in assessing cytotoxicity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Since the methanol leaf extract of Paullinia pinnata did not show any sign of toxicity against A. salina at 10, 100, and 1000 µg/mL, it implies that the extract may have no anti-tumor, pesticidal, anti-Trypanosoma cruzi or antifungal properties. This observation is inconsistent with the findings of the study conducted by de Dieu Tamokou et al (15), which showed that P. pinnata leaves had anticancer properties. This may be because these investigators employed various specific cancer cell lines, suggesting that cancer cell lines are more sensitive in assessing cytotoxicity.…”
Section: Discussioncontrasting
confidence: 99%
“…The methanol leaf extract of P. pinnata showed no significant activity against E. coli and B. subtilis, and had no activity against S. flexneri, S. aureus, P. aeruginosa, and S. typhi. This supports the findings of de Dieu Tamokou et al who investigated the leaf extract of P. pinnata for activity against Salmonella typhimurium, Listeria monocytogens, E. coli, and S. aureus but reported no activity (15). Our findings also corroborate the observations of Ajayi et al (42) who investigated essential oil extracted from P. pinnata but did not report any activity against Klebsiella pneumonia, Bacillus megaterium, B. subtilis, Proteus mirabilis, P. aeruginosa, and E. coli.…”
Section: Discussionsupporting
confidence: 90%
“…Herbal substances today symbolize safety in contrast to the synthetics that are regarded as unsafe to humans and the environment [48] [49]. With regard to the oral acute toxicity evaluation of G. suaveolens extracts, the lethal dose 50 was determined using Wistar female albino rats at the concentration of 2000 and 5000 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 99%
“…Rats had been given a nutritionally standard diet (rat food Nutrimix Esparto, El Badr Company, Utique-Bizerte, TN), with free access to tap water ad libitum and kept under controlled temperature (22 ± 2 °C) and 12/12 h light/dark cycle. To avoid interactions between sexual hormone fluctuations and digestive tract response, all the females were checked before treatment and chosen in diestrus phase [ 38 ].…”
Section: Methodsmentioning
confidence: 99%